HUBUNGAN PENGGUNAAN ALAT KONTRASEPSI HORMONAL DENGAN STABILITAS TEAR FILM : SEBUAH TINJAUAN NARATIF - Praja, Fathira Luthfi Nuresa; Hendriati, Hendriati; Elmatris, Elmatris; Vitresia, Havriza; Irawati, Lili; Mahata, Liganda Endo (SINERGI : Jurnal Riset Ilmiah, 2025)
Background : Tear film is a fluid-filled layer that protects the eyes from the external environment. This layer consists of three layers, namely lipid, aqueous and mucin. Tear film stability is seen as one of the main characteristics of eye health. failure to maintain balance Tear film can cause dry eyes. One of the causes of dry eyes is an imbalance of steroid sex hormones such as estrogen, progesterone and androgens. These hormones have mRNA receptors on the surface tissues of the eye that are susceptible to hormonal contraceptives. Objective : This literature study aims to explore various original research literature on the relationship between the use of hormonal contraceptives and the stability of Tear film.  Methods : Narrative reviews of literature searched through the Pubmed and Google Scholar databases, then selected based on established inclusion and exclusion criteria. Results : There are 6 literatures with 444 women of childbearing age with an age range of 20-45 years who use the TBUT and Schirmer examinations. Conclusion : There is no relationship between the use of hormonal contraceptives and the stability of tear film